Quality of Working Life on Residents Working in Hospitals - M Hosseini Zare; B Ahmadi; A Akbari Sari; M Arab; E Movahed Kor (Tehran University of Medical Sciences, 2012)
Background: Residents play an important role in the delivery of hospital care. They regularly work overnight, in emergency situations and with workload and stress which can affect their performance and quality of working life (QWL). This study explores the QWL and its contributory factors in residents working at hospitals affiliated with Tehran University of Medical Sciences (TUMS), Tehran, Iran. Methods: Medline was searched to identify questionnaires for measuring QWL in healthcare professionals and these questionnaires were used to design a comprehensive questionnaire for measuring residents QWL. Face and content validity of the questionnaire were examined by 7 experts. The questionnaire then was completed twice with one-week interval by 14 residents to assess the intera-rater reliability. Then 310 questionnaires were distributed among residents working at different specialties in 7 hospitals affiliated to TUMS including a large general hospital, two medium general hospitals and four small single specialty hospitals. Statistical analyses were performed by SPSS. Results: Totally, 263 residents (84%) completed the questionnaire. The quality of working life was very well in 18%, well in 32%, moderate in 31%, low in 14% and very low in 5% of residents. Pediatric residents had the highest and urology and internal medicine residents had the lowest quality of working life. Conclusion: The QWL is high in the majority of residents, but the QWL is still not desirable in a significant proportion of them. The questionnaire used in this study is reliable and valid. The residents' QWL still need improvement.